Professional and Ethical Responsibility of Syllabus Descriptions in the Medical (Schools: (Medicine and Dentistry), University of Sabah – Libya: As a Model) (Journal of Human Sciences, 2018)
This study focused on ethical responsibility and its relation to the scientific and practical preparation of the students in the medical colleges, through theoretical and practical courses. The objectives of this study aim to develop the student's sense of professional and moral duty and to explain the damage caused by professional errors of all kinds, in the academic year 2015-2016. The sample included 105 students, 89 women and 16 Men, who werenon- selected randomly. Comprehensive descriptive method is used. The study data were collected and analyzed by using the Statistical Program for Social Sciences (SPSS). The results of the study show the variables of the first axis, related to the ethical and professional dimensions which realized by medical students. These were in the direction of (I do not know). The second axis was based on conscious awareness about the importance of studying the   educational institutions ethics at the highest level. The results of the study have a significant impact on the level of practical training. The professional preparation of the point of view confirmed completely agreement with the same results of the previous studies in the same field. The results of the third and fourth axis showed that the medical responsibility of the provisions of Islamic law, ethics, status laws and professional practice, and the consequent penalties, resulted in moderate and weak trends.